2015
DOI: 10.1017/s0033291715001725
|View full text |Cite
|
Sign up to set email alerts
|

Preventing depression and anxiety in young people: a review of the joint efficacy of universal, selective and indicated prevention

Abstract: Depression and anxiety (internalizing disorders) are the largest contributors to the non-fatal health burden among young people. This is the first meta-analysis to examine the joint efficacy of universal, selective, and indicated preventive interventions upon both depression and anxiety among children and adolescents (5-18 years) while accounting for their co-morbidity. We conducted a systematic review of reviews in Medline, PsycINFO and the Cochrane Library of Systematic Reviews, from 1980 to August 2014. Mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
229
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(249 citation statements)
references
References 22 publications
16
229
1
3
Order By: Relevance
“…Further, depression is known for its recurrent course and its fluctuations in level of depression symptoms (Judd et al, 1998; Kennedy and Paykel, 2004; Van Rijsbergen, 2014). This implies that in some adolescents depression symptoms might recur after some time, despite the preventive intervention they received, which is also advocated in different meta-analyses (Stockings et al, 2016). Especially when there is no change in the risk factors, the risk for depression remains high.…”
Section: Discussionmentioning
confidence: 93%
“…Further, depression is known for its recurrent course and its fluctuations in level of depression symptoms (Judd et al, 1998; Kennedy and Paykel, 2004; Van Rijsbergen, 2014). This implies that in some adolescents depression symptoms might recur after some time, despite the preventive intervention they received, which is also advocated in different meta-analyses (Stockings et al, 2016). Especially when there is no change in the risk factors, the risk for depression remains high.…”
Section: Discussionmentioning
confidence: 93%
“…The dominant approach has been to take effective clinical treatments, such as cognitive-behavioural therapies (CBT), and apply these to the general population of adolescents or to at-risk subgroups to test if they prevent disorders developing. A systematic review and meta-analysis of RCTs 287 of prevention interventions for depression or anxiety in children and adolescents had mixed findings on the effectiveness of this strategy. The investigators concluded that these interventions produced minimal to moderate reduction in symptoms in the shortterm but no effect beyond 12 months of follow-up.…”
Section: Actions For Healthmentioning
confidence: 99%
“…Although digital and social media have been implicated as risk factors, online and mobile-phone interventions could play a positive part in prevention and promotion of access to clinical services. 287 …”
Section: Actions For Healthmentioning
confidence: 99%
“…It is acknowledged that young people are less likely to seek help for mental health problems if they have negative attitudes towards seeking help, if they feel they should be able to resolve the issue themselves and if they are experiencing suicidal ideation [18]. Accessing help for mental health problems is recognised as a protective factor [18] with indicated and early intervention programs likely to be most beneficial to adolescents and young adults [18, 19]. …”
Section: Introductionmentioning
confidence: 99%